2018
DOI: 10.1097/igc.0000000000001240
|View full text |Cite
|
Sign up to set email alerts
|

Robotic vs Open Surgery for Endometrial Cancer in Elderly Patients: Surgical Outcome, Survival, and Cost Analysis

Abstract: Elderly women can safely undergo robotic surgery for endometrial cancer and could be offered this technique to the same extent as younger patients. They may benefit from shorter hospital stay, decreased blood loss, and postoperative complications, without resulting in higher costs to the health care system or jeopardizing their survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 46 publications
3
24
1
Order By: Relevance
“…Comparing the costs of RS with the use of disposable equipment and yearly maintenance costs, averaged according to 350 procedures a year, found no significant difference in cost, when compared to laparotomy. Recent research conducted in Sweden [ 21 ] presented very similar costs between these two procedures (robotic € 10,683 and laparotomy € 11,073, P = 0.367) for the same type of cancer. Another study [ 22 ] with a sample of 120 patients, showed that healthcare costs for robotic-assisted laparoscopic surgery were significantly lower (€15,581 vs. €16,807, P < 0.05) than for laparotomy.…”
Section: Discussionmentioning
confidence: 94%
“…Comparing the costs of RS with the use of disposable equipment and yearly maintenance costs, averaged according to 350 procedures a year, found no significant difference in cost, when compared to laparotomy. Recent research conducted in Sweden [ 21 ] presented very similar costs between these two procedures (robotic € 10,683 and laparotomy € 11,073, P = 0.367) for the same type of cancer. Another study [ 22 ] with a sample of 120 patients, showed that healthcare costs for robotic-assisted laparoscopic surgery were significantly lower (€15,581 vs. €16,807, P < 0.05) than for laparotomy.…”
Section: Discussionmentioning
confidence: 94%
“…Surgery is often avoided altogether in some high‐risk scenarios leading to significant undertreatment. Although most studies in these populations are retrospective, similar outcomes have been observed with decreased morbidity associated with laparoscopic surgery . In a retrospective analysis of patients from the Gynecologic Oncology Group LAP2 trial randomizing patients to laparotomy vs laparoscopy, patients greater than 60 years old experienced significantly less morbidity in the laparoscopic group.…”
Section: Current Indicationsmentioning
confidence: 87%
“…However, it's important to highlight that the surgery in elderly women is not contraindicated only by age factor, in relation to its potential benefit [25]. Mini-invasive surgery and robotic laparoscopy demonstrated a large benefit in elderly women in terms of reduction of complications [26,27]. Also, in consideration of any possible role of neaodiuvant chemotherapy and radiotherapy, Eggeman et al, [28] in their work, described that elderly women with EC generally refuse this kind of treatment because radiotherapy and chemotherapy are not recommended by the physicians, in relation of performance status and medical diseases of the patients.…”
Section: Discussionmentioning
confidence: 99%